Istanbul in the Shadow of Inflation (1914-1921) - Doygun, Ecem (HACETTEPE UNIV, 2022)
This study analyzes the inflation experienced during the First World War and its effects, on the basis of average living expenses of a nuclear family of four people in Istanbul. During this analysis, the changes in the prices of basic food products such as bread, flour, oil, sugar, rice; lighting, heating, and housing expenses; as well as apparel in 1914 and 1921 will be compared. The category who were affected at most by the economic, political, and social changes experienced during this period, which covered the First World War and the Armistice period, was the people who tried to sustain their lives with a fixed income in consumption cities such as Istanbul. The subsistence of Istanbul, the capital of the Ottoman Empire, was of great importance for the Committee of Union and Progress. International trade declined and the needs of the army took priority upon the beginning of the First World War. During the war, various methods were tested by the intellectuals of the Union and Progress towards the problems of famine and the constant increase in food prices in Istanbul. Moreover, the food products required for the daily need of the city were sought to be supplied from the surrounding cities and Central Anatolia having a railway connection. Although famine and increase in prices were tried to be brought under control through methods such as report card called karne, it was not successful. The people had to struggle with high inflation not only during the war, but also after the war. The aim of this study is to examine how the people in the fixed income group living in Istanbul were affected by inflation, on the basis of their basic needs, in the conditions of the First World War and the Armistice period.
Keywords: Istanbul; inflation; First World War; National Economy; Public utilities; History